Adams Inlet, Nunavut -- photograph - Seale, Linda N. (2000)
View NW from Nanisivik airstrip on the Borden Peninsula, northern Baffin Island, Nunavut : Adams Inlet, St Georges Society Cliffs : Admiralty Inlet and Brodeur Peninsula beyond. August 2000